2012
DOI: 10.1039/c2jm30992k
|View full text |Cite
|
Sign up to set email alerts
|

Conducting polymer alloys for photo-enhanced electro-catalytic oxygen reduction

Abstract: Electro-catalysis is a core element in many technologies proposed for energy storage and conversion in a post-petroleum energy landscape. This has prompted the development of new electro-catalysts, for example for fuel-cells, water-splitting cells, and metal-air batteries, which are not based on traditional rare metals such as platinum, palladium and iridium. In this context, the possibility to use organic conjugated polymers to replace inorganic catalysts has shown promising progress. We hereby demonstrate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…[16][17][18][19][20][21][22] By combining their electrocatalytic activity and photophysical properties, conducting polymers have become efficient light-enhanced catalysts for ORR in more recent research works. [23][24][25] Winther-Jensen and co-workers demonstrated that an "alloy" of PEDOT and polythiophenes shows electrocatalytic activity towards ORR. This activity could be enhanced significantly under visible-light illumination.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…[16][17][18][19][20][21][22] By combining their electrocatalytic activity and photophysical properties, conducting polymers have become efficient light-enhanced catalysts for ORR in more recent research works. [23][24][25] Winther-Jensen and co-workers demonstrated that an "alloy" of PEDOT and polythiophenes shows electrocatalytic activity towards ORR. This activity could be enhanced significantly under visible-light illumination.…”
mentioning
confidence: 98%
“…In a simple fuel-cell, the lightenhanced current could be maintained over long periods, attributed to the durability of the heterojunction of light-harvesting polythiophene and hole-conducting PEDOT. [25] Despite their remarkable performance in polymer solar cells, dye-sensitized solar cells, and dissolved oxygen sensors, the use of polythiophenes for photoenhanced cathodes in BFCs has rarely been reported up to now. Actually, they are promising candidate materials for cathodic catalysts because of their high stability, low costs, and ease of preparation.…”
mentioning
confidence: 99%
“…For example, Kolodziejczyk and co-workers [39] studied a new heterojunction design involving alloys of two conjugated polymers, PEDOT and polyterthiophene (PTTh), as a light-assisted catalyst of (1) oxygen reduction (to form water) and (2) water oxidation (to form oxygen). In acting as an oxygen reduction photocatalyst, the mixed polymers, deposited using the VPP method on either bulk gold or on Goretex sputter coated with gold, exhibited excellent performance, with stability lasting up to 98 h. However, this photocatalyst did not display a notable water oxidation effect, likely due to the recombination reactions.…”
Section: Solar Water Splitting Using Poly(34-ethylenedioxythiophene)mentioning
confidence: 99%
“…[5] As such, it seemed feasible that photogenerated electrons may promote the complete reduction of oxygen to water. Winther-Jensen and co-workers [6] have reported that the activity of electrocatalytic ORR could be enhanced by illumination of two conjugated organic catalysts (PEDOTa nd polythiophene). Dong [7] and co-workers showed that light irradiation enhanced the performance of biofuel cells when using aphotoresponsive cathode.Herein, we describe that the ORR activity is greatly enhanced upon illumination of ap olyterthiophene (pTTh) electrode.The onset potential was positively shifted from 0.66 to 1.34 V, and the current was enhanced by af actor of 44 at 0.6 V. Ap roof-of-concept light-driven H 2 -O 2 fuel cell was then assembled;u pon illumination, the V oc increased from 0.64 to 1.18 V, and the J sc value was doubled as well.…”
mentioning
confidence: 99%
“…[5] As such, it seemed feasible that photogenerated electrons may promote the complete reduction of oxygen to water. Winther-Jensen and co-workers [6] have reported that the activity of electrocatalytic ORR could be enhanced by illumination of two conjugated organic catalysts (PEDOTa nd polythiophene). Dong [7] and co-workers showed that light irradiation enhanced the performance of biofuel cells when using aphotoresponsive cathode.…”
mentioning
confidence: 99%